2015
DOI: 10.14740/jnr339w
|View full text |Cite
|
Sign up to set email alerts
|

Human Embryonic Stem Cells in Treatment of Spinal Cord Injury: A Prospective Study

Abstract: Background: Spinal cord injury (SCI) is a devastating disease which impacts the patient physically, psychologically and financially. Although the pharmacological and non-pharmacological methods are used, none of them are able to improve the quality of life permanently. Recent advancement in the regenerative medicines has risen a new dawn for treatment of SCI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…The treatment modalities of these diseases [3]. Embryonal stem cells (ESCs) are the best source of omnipotent stem cells as they have an unlimited potential to produce any specialised cell type of an organism [3,16].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The treatment modalities of these diseases [3]. Embryonal stem cells (ESCs) are the best source of omnipotent stem cells as they have an unlimited potential to produce any specialised cell type of an organism [3,16].…”
Section: Resultsmentioning
confidence: 99%
“…Experimental results suggest the almost unrestricted capacity for their utilisation in replacement therapy and regenerative medicine [16,17]. On the other hand, the fact that a blastocyst developing from a fertilized egg has to be is recommended [7].…”
Section: Resultsmentioning
confidence: 99%
“…33 In our previous study, we have observed remarkable clinical improvements in 11 SCI patients with hESC therapy. 34…”
Section: Discussionmentioning
confidence: 99%
“…[17][18][19][20][21] We recently reported a remarkable clinical improvement in 11 patients with SCI treated with hESC therapy in a prospective study. 22 We have also reported the safety and efficacy of hESC therapy in patients with cerebral palsy, cortico-visual impairment, Friedrich ataxia, Lyme disease, spinocerebellar ataxia, and Duchenne muscular dystrophy. [23][24][25][26][27][28] In this paper, we present the retrospective evaluation of our patients with SCI treated with hESC therapy.…”
mentioning
confidence: 96%